2018
DOI: 10.3390/vetsci5010024
|View full text |Cite
|
Sign up to set email alerts
|

Application and Comparative Evaluation of Fluorescent Antibody, Immunohistochemistry and Reverse Transcription Polymerase Chain Reaction Tests for the Detection of Rabies Virus Antigen or Nucleic Acid in Brain Samples of Animals Suspected of Rabies in India

Abstract: Accurate and early diagnosis of animal rabies is critical for undertaking public health measures. Whereas the direct fluorescent antibody (DFA) technique is the recommended test, the more convenient, direct rapid immunochemistry test (dRIT), as well as the more sensitive, reverse transcription polymerase chain reaction (RT-PCR), have recently been employed for the laboratory diagnosis of rabies. We compared the three methods on brain samples from domestic (dog, cat, cattle, buffalo, horse, pig and goat) and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Another advantage of the molecular approach is a better sensitivity in case of putrefied samples, which are often unfit for the detection of viral antigens [31]. This is an important factor in the African setting, where the arrival of field samples to diagnostic facilities can be delayed due to transportation issues, samples can be incorrectly stored [10] or suspected animals can be exhumed several weeks after their burial following suspicion of human rabies cases [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of the molecular approach is a better sensitivity in case of putrefied samples, which are often unfit for the detection of viral antigens [31]. This is an important factor in the African setting, where the arrival of field samples to diagnostic facilities can be delayed due to transportation issues, samples can be incorrectly stored [10] or suspected animals can be exhumed several weeks after their burial following suspicion of human rabies cases [32].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important factor in the African setting, where the arrival of field samples to diagnostic facilities can be delayed due to transportation issues, samples can be incorrectly stored [10] or suspected animals can be exhumed several weeks after their burial following suspicion of human rabies cases [32]. Although real-time RT-PCR protocols that detect smaller fragments is a better option for detection of the viral genomes in case of advanced decomposition [32], a recent study from India [31] showed that out of thirty six [36] field putrefied samples unfit for detection of viral antigens by either DFA test or dRIT, thirty five [35] of them still tested positive by mean of a well-known hemi-nested RT-PCR also targeting rabies virus N gene [33]. In any case, although opting for molecular testing increases the possibility to identify the virus in putrefied material, it is not exempt from misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prabhu et al. (2018) compared the dRIT with the dFAT and RT‐PCR techniques performed in brain from wild and domestic animals from various parts of India, among them, only five horses. These authors demonstrated that 167/257 (65%) samples were found positive by all three tests; however, the viral variant was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…The dRIT was developed in the late 1990s at the Centers for Disease Control and Prevention (CDC) in Atlanta (USA) (Rupprecht et al., 2014). Subsequent investigations have demonstrated that the dRIT presents equal or higher diagnostic sensitivity and specificity than the dFAT (Coetzer, Sabeta, Markotter, Rupprecht, & Nel, 2014; Dürr et al., 2008; Madhusudana, Subha, Thankappan, & Ashwin, 2012; Mani & Madhusudana, 2013; Middel, Fehlner‐Gardiner, Pulham, & Buchanan, 2017; Patrick et al., 2019; Prabhu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation